BAP1 Immunohistochemistry and p16 FISH in the Diagnosis of Sarcomatous and Desmoplastic Mesotheliomas. (May 2016) - Hwang, Harry C.; Pyott, Shawna; Rodriguez, Stephanie; Cindric, Ashlie; Carr, April; Michelsen, Carmen; Thompson, Kim; Tse, Christopher H.; Gown, Allen M.; Churg, Andrew
Abstract : The separation of sarcomatous and desmoplastic mesotheliomas from benign organizing pleuritis can be morphologically very difficult. Deletion of p16 ( CDKN2A ) by fluorescence in situ hybridization (FISH) testing appears to be a reliable marker of malignancy in mesothelial proliferations, and more recently it has been reported that, in this setting, loss of BAP1 by immunohistochemistry is only seen in malignant mesotheliomas. To determine how useful these tests are with sarcomatous and desmoplastic mesotheliomas, we examined 20 such tumors. Loss of BAP1 was seen in 3/20 (15%) and deletion of p16 by FISH was seen in 16/20 (80%) cases. Loss of one or the other marker was observed in 17/20 (85%). We also examined 13 sarcomatoid carcinomas, an important differential diagnosis of sarcomatoid mesotheliomas, and found that BAP1 was never lost, but p16 was deleted in 3/11 (27%). We conclude that: (1) BAP1 immunohistochemistry is relatively insensitive in the context of sarcomatous and desmoplastic mesotheliomas, but as a matter of time and cost efficiency may nonetheless be a useful first approach to the problem; (2) deletion of p16 by FISH is considerably more sensitive, but there remain a proportion of cases in which p16 is not deleted; (3) a small improvement in sensitivity can be achieved by using both markers; (4) in the context of a spindle cell malignant tumor in the pleura or peritoneum, which morphologically might be a metastatic sarcomatoid carcinoma or a mesothelioma, the finding of BAP1 loss favors mesothelioma, but p16 FISH cannot be used to separate sarcomatous mesotheliomas from sarcomatoid carcinomas.